2006
DOI: 10.1111/j.1532-5415.2006.00921.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Alanine Aminotransferase Activity in Older People Is Associated with Greater Long‐Term Mortality

Abstract: ALT activity represents a strong and independent surrogate marker for mortality in community-dwelling elderly men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
91
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(111 citation statements)
references
References 46 publications
16
91
4
Order By: Relevance
“…Our results are consistent with many studies that have shown that elevated liver markers are not only sensitive indicators of hepatobiliary diseases and alcohol consumption, but even within reference range, as in the present study, are associated with a variety of common diseases, such as CAD, AF, DM, dementia, PD [28][29][30][31][32][33], and mortality [34][35][36][37] independently of alcohol consumption. Reported in the literature age and gender-based differences in liver [32,[34][35][36] and bone turnover markers [38][39][40][41][42], as well as in three studied adipokines [43][44][45][46] were confirmed within our study population, specifically, the decrease of transaminase activities and increase of bone turnover (OC and NTx/Cr) with ageing, and higher levels of urinary bone resorption markers and circulating adiponectin and leptin in women than in men.…”
Section: Liver-bone Interactionssupporting
confidence: 81%
See 2 more Smart Citations
“…Our results are consistent with many studies that have shown that elevated liver markers are not only sensitive indicators of hepatobiliary diseases and alcohol consumption, but even within reference range, as in the present study, are associated with a variety of common diseases, such as CAD, AF, DM, dementia, PD [28][29][30][31][32][33], and mortality [34][35][36][37] independently of alcohol consumption. Reported in the literature age and gender-based differences in liver [32,[34][35][36] and bone turnover markers [38][39][40][41][42], as well as in three studied adipokines [43][44][45][46] were confirmed within our study population, specifically, the decrease of transaminase activities and increase of bone turnover (OC and NTx/Cr) with ageing, and higher levels of urinary bone resorption markers and circulating adiponectin and leptin in women than in men.…”
Section: Liver-bone Interactionssupporting
confidence: 81%
“…These findings are in contrast with the widespread (based mainly on animal studies) view that leptin acting primarily through the centrally (hypothalamus and brainstem) mediated pathways suppresses bone formation [14,71,72], but are in accord with some, but not all [34,44,[73][74][75][76], clinical studies that reported a positive association between serum leptin and OC levels [77,78] and with experiments showing that peripheral leptin increases osteoblast proliferation, differentiation and activity, inhibits osteoclast activity and bone resorption, increasing bone mass [79][80][81]. Furthermore, a meta-analysis (59 studies) found that leptin was positively associated with bone mineral density (BMD) and high levels of leptin were predictive of lower risk of fractures [82].…”
Section: Adipokines and Markers Of Hepatic Mineral And Bone Metabolismcontrasting
confidence: 56%
See 1 more Smart Citation
“…However, no subanalysis was performed on the nondiabetic group for CVD-related death only; therefore, these results are not as pure as the other two studies. It appears that any proposed linear relationship between ALT and incident CVD is debatable, as others have recently shown that ALT may in fact exhibit a U-shaped association with total mortality 24,25 and unpublished data from our group (Ford et al) suggests that ALT's associations with CVD events may be similarly shaped with increased risk also apparent at low ALT concentrations. Thus, current evidence goes against a linear association of ALT with CVD events.…”
mentioning
confidence: 81%
“…In patients with a priori elevated transaminases this is further complicated due to the lack of guidelines as to what contributes a significant increase [Schenker et al 1999]. In older people, reduced liver size may mean transaminases do not increase as substantially as in younger people [Elinav et al 2006;Le Couteur and McLean, 1998]. …”
Section: Laboratory Detectionmentioning
confidence: 99%